Fatores intervenientes na perda da qualidade de vida: o setor de transporte e cargas - Quilici, Ricardo Francisco Marques (2008)
Given the importance the Quality of Life at Work has in de Brazilian work force, this survey’s goal was to study which factors lead the workers to stay away from work and consequently lose their Quality of Life (QL) in the city of Ponta Grossa - PR. In this survey, the following have been analyzed: 1. the most frequent diseases that lead to workers absence at work; 2. the level of loss of QLW in the employees and 6. the factors that interfere in their (QL), in the sectors with the greatest number of benefits. In order to assess the goals, the following question has been proposed: What are the most frequently pointed reasons, by the workers, for the loss of QL and its intervenient factors? This survey used quality criteria, through data of “INSS” during the years of 2005 and 2006 and quality, through the “WHOQOL-100” questionnaire the acquired result was: the most frequent diseases are the ostheomuscular and conjunctive tissue, the workers presented disappointment to wards their work environment and what interfered in their QL was pain and discomfort. This research pointed out the importance of implementing programs of this productive sector.